A study of adherence to treatment and influencing factors it in patients with ischemic heart disease (Texas Journal of Multidisciplinary Studies, 2024)
Adherence to treatment in patients with ischemic heart disease was studied. The study was conducted in 108 patients aged 55-68 years. A special questionnaire was distributed to each patient and the obtained results were studied. Adherence to treatment was compared between stented patients and drug-only patients. Also, in order to study the factors affecting patients' adherence to treatment, a special questionnaire was prepared and the patients' answers were recorded. In this way, the most important factors affecting the adherence of patients to treatment were determined.